Pengujian Sifat Mekanis Kayu Lulu (Celtis latifolia Planc) pada Dua Kondisi Kadar Air asal Manokwari Papua Barat (Testing for Wood Mechanical properties of Lulu (Celtis latifolia Planc) on Two Moisture Contents Collected from Manokwari Papua Barat) - Wahyudi Wahyudi; F A Wospakrik; B B Rettob (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
The mechanical properties of Lulu (Celtis latifolia Planch.), namely MOE, MOR, compression paralell and perpendicular to grain, respectively, tested on two moisture contents condition. Wood sample was collected from Manokwari Papua Barat. Experiments were designed with factorial nested design experiment. Three factorial treatments were axial of tree, pith to bark of tree, and two moisture contents condition, and four replications were employed. The results show that MOE, MOR, compresion parallel to grain were not significantly different among vertical axis of trees, except for compression perpendicular to grain. From bark to pith, all mechanical wood tested were statistically not different. However, air-dried samples tend to produce higher values for all mechanical wood properties tested. According to Indonesian classification grade, lulu wood (Celtis sp) is classified into class I for MOR, and MOE, whereas class II is for compression parallel to grain. Using its specific gravity, this wood is belonging to the class II or heavy wood. The values of compresion parallel to perpendicular grain is 3.29 higher. In addition, this wood species could be used as alternative contruction housing material , mainly indoor contruction and substituent timbers.Keywords: Lulu (Celtis spp), mechanical properties, moisture contents, Papua Barat